2020
DOI: 10.3390/diagnostics10080598
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Receptor PET/CT Imaging for the Detection and Staging of Pancreatic NET: A Systematic Review and Meta-Analysis

Abstract: We investigated the diagnostic performance of Somatostatin Receptor Positron Emission Tomography/Computed Tomography (SSR-PET/CT) for the detection of primary lesion and initial staging of pancreatic neuroendocrine tumors (pNETs). A comprehensive literature search up to January 2020 was performed selecting studies in presence of: sample size ≥10 patients; index test (i.e., 68Ga-DOTATOC or 68Ga-DOTANOC or 68Ga-DOTATATE PET/CT); and outcomes (i.e., detection rate (DR), true positive, true negative, false positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 68 publications
1
41
0
Order By: Relevance
“…The increase in SSTR PET/CT scans prompt to a better understanding of physiological uptake and pitfalls to minimize the number of unnecessary follow-up investigations [1][2][3][4]. In that setting, the physiological radiopharmaceutical uptake in the pancreatic head and UP on SSTR PET/ CT should be recognized and further investigations should only be done in case of a strong suspicion of malignancy especially in patients with NETs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in SSTR PET/CT scans prompt to a better understanding of physiological uptake and pitfalls to minimize the number of unnecessary follow-up investigations [1][2][3][4]. In that setting, the physiological radiopharmaceutical uptake in the pancreatic head and UP on SSTR PET/ CT should be recognized and further investigations should only be done in case of a strong suspicion of malignancy especially in patients with NETs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine tumors (NETs) originate from neuroendocrine cells and are more frequently located in small intestine and pancreas [1,2]. Recently, there has been an increase in the use of somatostatin receptor-based positron emission tomography/computed tomography (SSTR PET/CT) in the setting of NETs including pancreatic tumors [3,4]. The identification and localization of pancreatic NETs using SSTR PET/CT might affect patient medical and surgical management [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been recommended most recently to replace SRI with 111 In-pentetreotide SPECT/CT by 68 Ga-DOTA-SSA PET/CT since it has a higher diagnostic accuracy and sensitivity and requires a smaller dose of radiation (45,54,55). However, a recently published meta-analysis, which only included pNET patients, that evaluated the detection of the primary lesion and its primary staging with 68 Ga-DOTA-SSA PET/CT demonstrated that the pooled specificity and sensitivity for identifying primary pNET was 95 and 79.6%, respectively (64). This sensitivity was lower compared to the results of other meta-analysis/ series, which included patients with different type of NETs, and demonstrated a mean sensitivity of 92% (range between 68 and 100%), a relatively high mean specificity of 88% (range between 50 and 100%), and a high mean accuracy of 93% (range between 90 and 97%) (50,54,55,(65)(66)(67)(68)(69).…”
Section: Sstr-targeted Imaging In Pnetsmentioning
confidence: 99%
“…Importantly, the latter was not detected on prior CT imaging. The increased sensitivity of Ga68-DOTATATE PET/CT allowed detection of this additional tumor [ 12 ]. Based on tumor locations, the patient was deemed a good surgical candidate for a laparoscopic radical antegrade modular pancreatosplenectomy (RAMP).…”
Section: Case Presentationmentioning
confidence: 99%